La Nouvelle France : the making of French Canada : a cultural history - Moogk, Peter N., 1943- (Michigan State University Press, 2000)
"Moogk draws on a rich body of evidence - literature; statistical studies; government, legal, and private documents in France, Britain, and North America - to define the colonists' character. In so doing, he has discovered a New France vastly different from the one portrayed in popular history. Aboriginal people looked upon the first white newcomers with disdain rather than with awe. French relations with allied Native Peoples were not consistently harmonious, but were strained and fragile. Most immigrants to the colony were not rebels; they were reluctant exiles from their homeland, speaking various languages and French dialects, and a third or more returned to Europe. Even those who remained in North America were socially conservative and developed their own institutions only when government neglect permitted it. The monarchy and Roman Catholicism molded attitudes and were as important as language in defining Acadian and Franco-Canadian identities. Moogk did not find a single entity called New France but a chain of loosely connected outposts stretching from Newfoundland in the east to the Illinois Country in the west. Yet the shared experience of being in the French Bourbon empire marked modern French Canada and, in particular, the Province of Quebec. La Nouvelle France is a starting point for understanding Quebec nationalism and the cultural values that give rise to it."--Jacket.